PENGEMBANGAN E-LKPD DENGAN PENDEKATAN MIND MAPPING UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA DI KELAS 5 SD - Maulidya, Vira; Sri Rahayu; Nyamik Rahayu Sesanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted to develop an electronic student worksheet (E-LKPD) designed using a mind mapping approach as an effort to enhance students’ learning motivation in mathematics, particularly on three-dimensional geometry topics for fifth-grade elementary school students. The research employed a Research and Development (R&D) methodology using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The participants of this study were fifth-grade students of SDN Pulungdowo 3 Tumpang. Data were collected through validation sheets, student response questionnaires, and learning motivation test instruments. The findings indicate that the developed E-LKPD meets the criteria of validity, practicality, and effectiveness. The implementation of the E-LKPD was able to improve students’ learning motivation, as reflected in increased participation, interest, and positive responses during the learning process. Therefore, the mind mapping–based E-LKPD is considered appropriate for use as an alternative instructional medium in elementary mathematics learning.